Analysis of English Teachers’ Assessment Strategies within Differentiated Learning Context at SMP NEGERI 2 SAWAN - Dewi, Kadek Andi Suari; Wahyuni, Luh Gede Eka; Paramartha, Anak Agung Gede Yudha (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study is intended to identify assessment strategies that are conducted by English teachers within differentiated learning contexts at SMP Negeri 2 Sawan. This study used a qualitative method with descriptive research design. The data were obtained through observation and interview with three English teachers at SMP Negeri 2 Sawan. The finding of study showed that English teachers at SMP Negeri 2 Sawan have conducted variety of assessment strategies such as Elicitation, Reviewing, Games, Question and Answer, Group discussion, Peer discussion, Exercise, Feedback, Presentation, Peer tutoring, Summarizing, Task, Test and Portfolio. Those assessment strategies were used to measure students’ learning process and provide feedback. In addition, it was found that teachers at SMP Negeri 2 Sawan conducted differentiated assessment only on assessment as learning and assessment for learning that have a function as formative assessment. Those assessment strategies with differentiation were dominant, conducted in the form of differentiation of process, where the teachers accommodated the students’ preferences to understand the material.